La medicina darwiniana como teoría científica dentro del campo de la teoría de la selección natural - Mercado Martínez, Pedro Estuardo (2007)
This work evaluate the level of Darwinian Medicine science, at means to be considered as a scientific theory incised the field of the natural selection theory. It does a begining review about the science and scientific method. It analyses some theories refered to science and it defines and characterise to pseudosience. Our methodology used consists f various methodologies and techniques to measure the level of the Darwinian Science through scientific evidences and gelting down conceptual techniques. We suggest as results: the axiom of the Darwinian Medicine through hypothesis; and epistemological criteria based on hypothetical and deductive method. We conclude that the Darwin Medicine has hypothesis which infer theories. They have names and theoretical terms, basic idias and formal requirement. Could be contrasted applyerig criteria and operations conceptual. Have level universality, it is a distinguished science of the pseudoscience; meanwhile, the Darwinian Medicine has the whole characteristics to be considered a scientific theory within the field of the natural selection.